Impact of increasing antimüllerian hormone level on in vitro fertilization fresh transfer and live birth rate - Kelly S. Acharya, M.D; Benjamin S. Harris, M.D., M.P.H; Jeremy M. Weber, M.S; Tracy Truong, M.S; Carl Pieper, Dr.P.H; Jennifer L. Eaton, M.D., M.S.C.I (Elsevier, 2022)
Objective: The objective of our study was to assess the association between AMH and live birth among women with elevated AMH undergoing first fresh IVF. Serum antimüllerian hormone (AMH) correlates with oocyte yield during in vitro fertilization (IVF). However, there are limited data regarding IVF outcomes in women with elevated AMH levels. Design: Retrospective cohort study using the Society for Assisted Reproductive Technology Clinical Outcomes Reporting System database from 2012-2014. Setting: Fertility clinics reporting to Society for Assisted Reproductive Technology. Patient(s): First, fresh, autologous IVF cycles with elevated AMH levels (≥5.0 ng/mL). Subanalyses were performed to examine patients with or without polycystic ovary syndrome (PCOS). Intervention(s): None. Main Outcome Measure(s): Odds of live birth. Result(s): Our cohort included 10,615 patients with elevated an AMH level, including 2,707 patients with PCOS only. The adjusted odds of live birth per initiated cycle were significantly lower per each unit increase in the AMH level (odds ratio, 0.97; 95% confidence interval, 0.96-0.98). Increasing AMH level was associated with increased cancellation of fresh transfer (odds ratio, 1.12; 95% confidence interval, 1.10-1.15) up to an AMH level of 12 ng/mL. The decrease in the live birth rate appears to be caused by the increasing incidence of cancellation of fresh transfer because the live birth rate per completed transfer was maintained. Similar trends were observed in the PCOS and non-PCOS subanalyses. Conclusion(s): Among patients with AMH levels of ≥5 ng/mL undergoing fresh, autologous IVF, each unit increase in AMH level is associated with a 3% decrease in odds of live birth because of the increased incidence of fresh embryo transfer cancellation.